2004
DOI: 10.1016/s0958-2118(04)00180-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration of organic solvents

Abstract: This article provides an insight into the mechanisms affecting solvent flux through dense membranes, and forms a basis for rejection studies of organic solute compounds from organic solvents. ABSTRACTTransport mechanisms and process limitations are relatively well understood for aqueous nanofiltration systems. Much work has also been done on the use of membranes for the removal of suspended matter from organic solvents. The removal of organic solute compounds from organic solvents using membrane technology has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
(22 reference statements)
2
21
1
Order By: Relevance
“…The permeation flux at 1 bar is 84.5 L m 2 h −1 and it increases quickly with rising pressure and reaches 89.2 L m 2 h −1 at 5 bar. The phenomenon of flux increasing with pressure has been observed in other reports also: n ‐hexane flux increased with pressure as reported by Bhanushali, flux of n ‐heptane and xylene (mixture of isomers) with pressure as reported by Robinson et al, flux of benzene and toluene went up with pressure was reported in White's study . This illustrates that pressure boost is an effective method for increasing permeation flux.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The permeation flux at 1 bar is 84.5 L m 2 h −1 and it increases quickly with rising pressure and reaches 89.2 L m 2 h −1 at 5 bar. The phenomenon of flux increasing with pressure has been observed in other reports also: n ‐hexane flux increased with pressure as reported by Bhanushali, flux of n ‐heptane and xylene (mixture of isomers) with pressure as reported by Robinson et al, flux of benzene and toluene went up with pressure was reported in White's study . This illustrates that pressure boost is an effective method for increasing permeation flux.…”
Section: Resultssupporting
confidence: 72%
“…In the literature, different solvent, solute and membrane parameters influencing the transport model were experimentally identified and different models were developed . However, transport models for Nanofiltration system are limited for specific experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the model used, the pore sizes were found to be of the same order of magnitude as sizes reported in the literature with only a few nanometers difference if any. The differences observed for the pore radii obtained through both models from two distinct pools of data (using either the values of solvent fluxes or the PEG retention results) may result from the roughness of the models (cylindrical pores, single diameter, etc.)…”
Section: Methodssupporting
confidence: 68%
“…The mechanisms of aqueous nanofiltration (NF) are fairly well documented but uncertainties remain about this process when organic solvents are used . This is mainly owing to additional solvent–solute–membrane interactions . Many studies have attempted to model mass transfer through such membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Sorption of solvents in polymers is a well studied phenomenon (Astarita and Joshi 1978;Robinson et al 2004) as it plays a major role in transport processes through dense membranes. Flory-Huggins thermodynamics theory is the most used approach to model this phenomenon (Flory 1953).…”
Section: Ensic Modelmentioning
confidence: 99%